Analysis of the scored goals in the soccer African cup of nations Ivory coast 2024 - SAOUDI, Ayoub; MERNIZ, Oussama (sports creativity, 2024)
The study aimed to analyze the pattern and trends of goals scored during the 2024 African Cup of Nations held in Ivory Coast, according to several indicators, namely the method of scoring goals, the time of scoring goals, the areas in which goals were scored, and finally the parts of the body in which goals were scored, in addition to knowing their percentage of the total goals scored. The researchers chose all the teams participating in the tournament as a sample for the study. They also used the descriptive approach, following the survey method due to its suitability to the nature of the study. They used the pedagogical observation network as a research tool through which videotapes containing all 119 goals scored in 52 matches were analyzed. The average goal scoring in the tournament was 2.29 goals per match, which is the highest compared to the previous two tournaments, Egypt 2019 and Cameroon 2022. Most of the goals were from open play, 72.27%, and 45.38% of the goals were scored in the last half hour of the match. Also, most of the goals were scored with the right foot. 53%, while most of it was within an area of ​​16.5 metres, or 72.27%.